Behavior of Consuming Blood Supplement Tablets Among Female Students of SMP Negeri 1 Kendari - Hartati Bahar (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Anemia is a medical condition characterized by a decreased number of red blood cells or hemoglobin levels below the normal range. It is often caused by micronutrient deficiencies and is prevalent among adolescent girls. One of the primary preventive measures is the administration of iron and folic acid supplements, commonly referred to as blood supplement tablets. In 2018, the coverage of blood supplement tablet distribution among adolescents in Indonesia reached 48.52%, surpassing the target set in the 2018 Strategic Plan, which was 25%. However, Southeast Sulawesi ranked 18th nationally, with a coverage rate of only 22.0%. Objective: This study aims to assess the knowledge, attitudes, and practices related to the consumption of blood supplement tablets among female students at SMP Negeri 1 Kendari. Methods: This research employed a descriptive survey design. The population consisted of 134 female students at SMP Negeri 1 Kendari, from which a sample of 100 was selected using a simple random sampling technique. Results: The findings indicate that 46% of the respondents possessed good knowledge regarding the importance of consuming blood supplement tablets, while 42% demonstrated poor knowledge. In terms of attitude, 41% exhibited a positive attitude, whereas 59% showed a negative attitude. Regarding practices, 41% of the students reported consuming blood supplement tablets, while 59% did not. Conclusion: A majority of the students (59%) did not consume blood supplement tablets, despite the known benefits for anemia prevention. Therefore, it is recommended that continuous education and awareness programs be implemented to improve knowledge and promote the regular consumption of blood supplement tablets among adolescent girls. Keywords: Anemia, Adolescents, Iron and Folic Acid Supplementation, Blood Supplement Tablets